Marker‐fusion PCR for one‐step mutagenesis of essential genes in yeast - Kitazono, Ana A.; Tobe, Brian T. D.; Kalton, Helen; Diamant, Noam; Kron, Stephen J. (Yeast (Chichester, England), 2002)
We describe a one‐step gene replacement method based on fusion PCR that can be used to mutagenize essential genes at their endogenous locus. Marker‐fusion PCR can facilitate transfer of alleles between strains as well as PCR‐based techniques, such as site‐directed and error‐prone PCR mutagenesis, all without cloning or strain constructions. With this method, PCR is used to fuse a mutagenized fragment to an overlapping fragment containing a selectable marker flanked by regions of homology to the target. By transforming yeast with these PCR products, specific mutations are introduced at the endogenous locus through homologous recombination. We tested the ‘marker‐fusion PCR’ method using the budding yeast CDC28 gene and were able to efficiently introduce site‐directed mutations and integrate genomic or plasmid‐borne mutant alleles. As a further application for this method, we used a spiked oligonucleotide to randomize the coding sequence for a single domain of CDC28 and were able to construct highly mutagenized libraries for this region. Copyright © 2002 John Wiley & Sons, Ltd.